Overlap between ADHD and Autism – Clinical and Genetic Evidence - Gill, Michael; Anney, Richard; Mulligan, Aisling (Current Psychiatry Reviews, 2014)
ADHD and Autism have been considered as two separate disorders and the classification systems make them mutually exclusive. However, there is a long-standing literature on overlapping phenotypes, and a more recent genetic literature on rare variants that have been found in both. This review summarises the clinical, familial and recent genetic overlap and discusses what this might mean for future diagnosis and treatment.
Keywords: genetic